Insider trading in Germany: Do corporate insiders exploit inside information? - Björn M. Dymke; Andreas Walter (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2006)
Our study analyzes a large sample of transactions carried out by corporate insiders reported to the German regulatory authority BaFin in the period July 1, 2002 to April 30, 2005 employing event study methodology. In particular, we focus on the question whether corporate insiders exploit inside information while trading in their company's stock. Therefore we use a distinct property of German law, i.e. company's obligation to reveal inside information through ad-hoc news disclosures, to link trading of insiders to their foreknowledge of important corporate news. We find strong evidence that insiders exploit inside information as they earn above average profits by front-running on subsequent news disclosures. Furthermore, looking at the type of insider, we find that members of the supervisory board (directors) and the group of other insiders (basically family members of senior managers and directors) profit substantially from exploiting inside information. In contrast, members of the executive board (senior managers) can be largely exculpated from exploiting inside information as they realize below average returns with their rare front-running transactions.
urn:nbn:de:bsz:21-opus-27380
Keywords: G11; G14; G30; 330; insider trading; inside information; 15a WpHG; German stock market; regulation of financial markets; Insiderhandel; Kapitalmarktrecht; Führungskräfte; Familie; Insiderrecht; Deutschland